Multiple Versions, Multiple Markets, Multiple Meanings: Worldwide Trade in British Autograph Replicas. Issue 3 (20th September 2022) - Codell, Julie
Abstract : In this essay I explore relationships between Victorian artists' prolific production of autograph replicas and the wide global demand for these replicas. Autograph replicas, defined by Victorian artists as variations on a subject through changes in size, medium or image from a first version, were largely commissioned by patrons. This market was later driven by foreign collectors who avidly sought autograph replicas, believed to be original works, not copies, to raise their own nations' cultural image in the world. The functions and demands for autograph replicas have unique historical and cultural contexts, including conflicts between artists and patrons. I describe artists' surreptitious studio practices producing these works and the unique effect autograph replicas had on collecting and on art history in the context of this special issue's rethinking of British art and the global. Autograph replicas challenged boundaries between original and copy and disrupted art‐historical notions of chronology, originality, canonicity, and market intervention.